انعكاسات الحرمان العاطفي الأمومي على شخصية الطفل - هاشيم, الطاوس (جامعة الوادي University of Eloued, 2017)
يهدف هذا البحث المكتبي إلى إبراز أهمية وجود الأم في حياة الطفل ومدى انعكاس واثر الحرمان العاطفي على شخصية الطفل في المجال النفسي، الانفعالي، الاجتماعي، المعرفي والسلوكي، بالإضافة إلى تحديد أهم العوامل المساهمة في الحرمان العاطفي الذي يترتب عنه معاناة الطفل من صراعات نفسية، احباطات، ضغوطات وقلق حاد نظرا للحاجة الماسة لوجود شخص بقربه يرعاه ويوفر احتياجاته في الطفولة. الحرمان العاطفي للطفل في السنوات المبكرة يحطم أسس النمو السليم عنده، نظرا لغياب الأم الكفيلة به، الشيء الذي يترك آثاره السلبية على طول مراحل حياته، علاقة الطفل بأمه في هذه الفترة لها الدور الأساسي في تشكيل شخصيته من خلال التفاعل القائم معها وإشباع حاجاته من عاطفة وامن، وعلى العكس الانفصال عنها أو الابتعاد عنها ينعكس سلبيا على صحته ما يكسبه شخصية مضطربة وغير سوية. This research aims at showing the importance of the mother’s presence in the child’s life and the reflections of maternal emotional deprivation on his personality at the psychological, emotional, social, cognitive and behavioral levels. In addition to identifying the most important factors contributing in the emotional deprivation, which leads to his suffering from: psychological conflicts, frustration and severe anxiety because of the critical need to the presence of someone to take care of him during childhood. Emotional deprivation of a child in the early years destroys the foundations of his healthy growth due to the absence of the mother to ensure it. This state leaves negative effects along the different stages of the child’s development. Through a based interaction with the mother, the relationship of the child to her in this period has a basic role in the formation of his personality,. The child thanks to this relationship satisfies his needs of affection and security. But on the other hand, separation or breaking away from the mother has negative impacts on his health, what constitutes a pathologic and an abnormal personality..
مقال
Keywords: الحرمان العاطفي؛ الشخصية; Emotional deprivation; Motherhood; Personality